The Relationship of Marital Status and The Implementation of Breast Self Examination on Women of Reliable Age - Indah Yun Diniaty Rosidi; Dahniar Dahniar (Journal of Ners and Midwifery, 2023)
Breast Self Examination is carried out to reduce breast cancer mortality by finding breast cancer as early as possible and treating it when the size is still small before the cancer metastasizes. The discovery of breast cancer as early as possible that is diagnosed and treated correctly will increase the life expectancy of breast cancer sufferers. The purpose of this study was to determine the relationship between marital status and the implementation of Breast Self Examination in women of childbearing age. This research was a descriptive analytic study with cross sectional and carried out in the Working Area of BPM Hj. Rismawati, Maros Regency, South Sulawesi. The sample used 37 respondents, namely women of childbearing age with cluster sampling technique and tested using Fisher's exact test . The result of this study showed that there was a significant relationship between marital status and the implementation of the Breast Self Examination. In this study it was also concluded that marital status was not a risk factor for the implementation of the Breast Self Examination (OR value 0.47 < 1) or it can be said that unmarried women only had 0.47 times the risk of not doing Breast Self Examination compared to women who had married. It is needed to do further research on the respondents' perceptions, respondents' socio-cultural or community about breast cancer and early detection of breast cancer and respondents' insurance status